1982
DOI: 10.1002/chin.198249309
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis and Biological Activity of Some Very Hydrophobic Superagonist Analogues of Luteinizing Hormone‐Releasing Hormone.

Abstract: Im Peptid Glu‐His‐Trp‐Ser‐Tyr‐Gly‐ Leu‐Arg‐Pro‐Gly‐NHQ (= LH‐RH) wird die 6‐Position durch die lipophilen D‐Amino‐ säuren (I) und (V) ersetzt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…We recognized that past SAR studies in the GnRH agonist series suggested that most D-amino acids at position 6 would influence potency in vivo favorably to about the same extent, [23][24][25] and that in the antagonists series the nature of this D-amino acid substitution may have a significant effect on duration of action. 11,26 The observation made earlier that compatibility of different acylating agents of the Aph 5 and DAph 6 and more particularly of Hor is important was vindicated in that the [Aph 5 (Hor)-DAph 6 (DHor)] substitution in 41 is more favorable than the corresponding [Aph 5 (Hor)-DAph 6 (Hor)] substitution in 30.…”
Section: Resultsmentioning
confidence: 99%
“…We recognized that past SAR studies in the GnRH agonist series suggested that most D-amino acids at position 6 would influence potency in vivo favorably to about the same extent, [23][24][25] and that in the antagonists series the nature of this D-amino acid substitution may have a significant effect on duration of action. 11,26 The observation made earlier that compatibility of different acylating agents of the Aph 5 and DAph 6 and more particularly of Hor is important was vindicated in that the [Aph 5 (Hor)-DAph 6 (DHor)] substitution in 41 is more favorable than the corresponding [Aph 5 (Hor)-DAph 6 (Hor)] substitution in 30.…”
Section: Resultsmentioning
confidence: 99%
“…2Nal had previously been utilized in structure/activity studies on tetragastrin and somatostatin analogs [80,81]. Subsequently was utilized in the design of superagonist LHRH analogs [82]. It may be recalled also that replacement of the Tyr 2 residue in OT and in AVP agonists with and 2Nal resulted in analogs which exhibited potent OT antagonism in vitro and in vivo in rat bioassays [45,52,53,[83][84][85].…”
Section: Introductionmentioning
confidence: 99%
“…47, No. 20 4811 procedures from 3,4,5-trimethoxybenzaldehyde, 27,28 while the 3,4-dimethoxy analogue, N R -Boc-3,4-L-dimethoxyphenylalanine, was from a commercial source. The phenylalanine derivatives were coupled to a to provide the Boc-protected dipeptides.…”
Section: Lettersmentioning
confidence: 99%